On Proclus and his influence in medieval philosophy - Bos, Egbert P., 1947-.; Meijer, P. A. (Philosophia Antiqua, 1992)
Proclus (c. 410 - 485) was one of the major Greek philosophers of late Antiquity. In his metaphysics he developed and systematized fundamental problems of Plato's thought, such as participation; transcendence - immanence; causation - participation - return; henads and monads. In a theological way he interpreted some of Plato's dialogues. In the tradition of the neo-platonic school of Athens he tried to bring together Orpheus, Pythagoras and Plato. Before and after his works had been translated into Latin, Proclus influenced the Christian West through the Liber de causis (\'Book of Causes\'), a Latin translation of an anonymous Arab version of his Elementatio theologica . Among those who commented on the Liber or on some of its theses, were many well-known philosophers: Albert the Great, Thomas Aquinas, Master Eckhart, Berthold of Moosberg and William of Ockham. The Liber de causis stimulated discussions about the concepts of God, first and second causality, universals, metaphysics of being as opposed to metaphysics of the one. In the volume various specialists discuss these problems: Saffrey, De Rijk, Meyer, Steel, De Libera, Aertsen, Beierwaltes and Bos.